The relationship between school physical activity policy environment and physical literacy among primary school students: evidence from Henan Province, China - Yin, Hang; Dev, Roxana Dev Omar; Soh, Kim Geok; Zhang, Yajing; Tan, Zhiyuan; Lian, Menglong (Public Library of Science, 2025)
Background Chinese primary school students spend the majority of their day at school, making the school physical activity policy environment (SPAPE) crucial to their development of physical literacy (PL). However, research exploring the relationship between SPAPE and PL remains limited. This study aims to investigate the association between SPAPE and students’ PL levels. Methods A total of 408 primary school students (206 boys and 202 girls) were included in the data analysis. The School Physical Activity Environment Questionnaire (SPAEQ) and the Canadian Assessment of Physical Literacy-Edition 2 (CAPL-2) were used to assess the policy environment and PL levels, respectively. Pearson correlation coefficients were calculated to explore the relationship between the policy environment and PL. Additionally, ANOVA and MANOVA analyses were conducted to examine the effects of age, gender, and their interaction on the relationship. Results A significant positive correlation was found between SPAPE and PL, with boys (r = 0.59, p < 0.01) and girls (r = 0.48, p < 0.01) both showing moderate to strong associations. MANOVA results revealed significant gender differences for Daily Behavior (DB) (F (1, 406) = 14.24, p < 0.01, partial η2 = .04) and Motivation and Confidence (MC) (F (1, 406) = 4.72, p < 0.05, partial η2 = .01). Significant age differences were observed for MC (F (4, 403) = 5.68, p < 0.01, partial η2 = .05) and Knowledge and Understanding (KU) (F (4, 403) = 8.57, p < 0.01, partial η2 = .08). No significant effects of age, gender, or interaction were found in relation to SPAPE. Conclusion This study is the first to explore the relationship between PL and SPAPE in Chinese primary school students. The results highlight the significant association between SPAPE and PL, with notable gender and age differences. These findings emphasize the importance of tailoring PA policies to account for demographic factors to effectively promote PL.